Criminal Justice and Security in Central and Eastern Europe: The United Nations Sustainable Development Goals – Rural and Urban Safety and Security Perspectives, Book of Abstracts (University of Maribor Press, 2023)
The fourteenth international biennial conference Criminal Justice and Security in Central and Eastern Europe, organised by the Faculty of Criminal Justice and Security, University of Maribor (UM FCJS) on 12–14 September 2023, is subtitled The United Nations Sustainable Development Goals – Rural and Urban Safety and Security Perspectives and addresses current challenges related to the UN SDGs and the provision of security in local communities. Topics of the conference are related to a research project of the UM FCJS on local safety and security – rural and urban perspectives (2019-20124) based on the UN SDGs that aim at the development of democratic societies trying to achieve seventeen ambitious goals globally. The conference is also a milestone that signifies thirteen years of membership of the UM FCJS in the United Nation’s Academic Impact Network (UNAI). The book of abstracts includes more than sixty abstracts of papers presented at the conference. The main topics of this year’s conference are rural criminology, criminal justice, policing, covid-19, crime, criminality, crime prevention, perception of crime, crime analysis, safety, security, community (oriented) policing, victimology and penology. Thanks for this great academic event go to the programme and organising committees, authors, participants and conference supporters nationally and internationally.